STUDI KOMPARASI TINGKAT INKLUSI KEUANGAN DI NEGARA ASEAN - Yana Raydhatul Jannah (Universitas Negeri Medan, 2017)
Financial inclusion programs in Asia began to intensify with focus on improving public access, especially those who have not yet enjoyed banking services. This makes financial inclusion one of the focuses of development in the financial sector in various countries, especially ASEAN, as a sound financial system can promote economic growth. This study aims to see the comparison of financial nclusion rates and see the effect of socio-economic variables on financial inclusion in ASEAN countries 2010-2015. In order to see the comparison of nclusion level of finance in each ASEAN country, the Index of Financial Inclusion (IFI) method was developed by Sarma (2008), while to examine the relationshipbetween socio-economic variables to financial inclusion, the Ordinary Least quare (OLS) method was used estimation techniques in the Random Effects Model approach. The results show that in general, financial inclusion in ASEAN countries is mainly influenced by the dimension of a disorder. In addition, only per-capita GDP variables are not significant partially. While other variables, namely population over 15 years, unemployment rate, and the number of people n rural areas have a significant influence on index of financial inclusion.